The clinicopathologic and immunohistochemical features of 60 cutaneous glomus tumor: a retrospective case series study - Yuehua Sun; Ruiqun Qi; Ze Wu; Xiaodong Zhang; Jun Niu (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background Glomus Tumor (GT) are benign neoplasms that originate from mesenchymal cells. It presents as tenderness and cold allodynia in the digits, especially in the subungual region. There are a few studies that investigated the mechanism of pain. Objectives To analyze the clinical-pathologic characteristics of GT and to identify the expression of IL-1β, IL-6, and CGRP in it, further, to explore the possible mechanism of pain. Methods The clinical and pathological data of 60 GT patients were retrospectively analyzed. Tissue microarrays and immunohistochemistry were used to measure the expression of IL-1β, IL-6 and CGRP. Results GT is more common in females and the ratio of male to was near to 1:2, mostly in middle-aged people. It often occurs in fingertips, especially the thumbs. Patients often present with spontaneous pain, tenderness, and cold hypersensitivity. Both the two pain mediators IL-1β and IL-6 were highly expressed in GT cells of patients with and without cold hypersensitivity. While CGRP was not expressed in GT. Study limitations Low sample size and further research is needed to explore the specific mechanism. Conclusions IL-1β and IL-6 were highly expressed in GT cells, suggesting that IL-1β and IL-6 have certain nociceptive roles in GT. In the 4 patients with cold intolerance, the intensity of IL-1β and IL-6 staining was also strong, suggesting that they may not play a role in the cold hypersensitivity. However, since there are only 4 patients with cold intolerance, it's necessary to conduct further in-depth research using a larger sample size. The specific role of CGRP in GT has not been found yet.